2011
DOI: 10.1007/s10995-011-0919-1
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Data Reporting on Postpartum Hemorrhage: Under-Estimates Recurrence and Over-Estimates the Contribution of Uterine Atony

Abstract: (250 words)Objectives: This study aimed to explore whether recording of a prior adverse pregnancy outcome in a medical record increases the likelihood that recurrence of the same event is reported in population data. Methods:Using a random sample of 294 women who had first and second pregnancies in NSW, and a postpartum hemorrhage (PPH) reported for at least one pregnancy, we compared 'coded' recurrence rates in hospital data with those obtained from medical record audit. 'Coded' recurrence in a second pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Women with a history of PPH had 4.94-fold increased odds of SPPH. Likewise, a study from Australia reported a recurrence rate of 28% from medical audits [27]. A study from Sweden reported that the recurrence of PPH might be explained by environmental and genetic factors [28].…”
Section: Risk Factors For Spphmentioning
confidence: 99%
“…Women with a history of PPH had 4.94-fold increased odds of SPPH. Likewise, a study from Australia reported a recurrence rate of 28% from medical audits [27]. A study from Sweden reported that the recurrence of PPH might be explained by environmental and genetic factors [28].…”
Section: Risk Factors For Spphmentioning
confidence: 99%
“…Having a history of PPH may be less well-reported to the registries than in our data sources. Likewise, a validation study from Australia [28] reported a recurrence rate of 28% from medical record audits, while the reported recurrence rate in register based data was 18%. The causes of PPH recurrence were investigated in a population study from Sweden [27].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…False reporting of cases caused by retained placental tissue as atonic bleeding in registries could explain this discrepancy. In a validation study examining the contribution of uterine atony to PPH [28], the incidence of uterine atony was overestimated by 10% when registry data were compared with clinical data. Access to detailed medical information enabled us to accurately estimate the proportion of cases with placental problems in our population.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…We utilised data collected in a review of PPH among 294 women with first and second pregnancies (representing 588 pregnancy records) and at least one PPH. The details of this study are reported elsewhere . Briefly, state birth data were used to select a random sample of 600 first and second birth records for 300 women giving birth in a selected Area Health Service in New South Wales (NSW) (2002–2006), and hospital separation data were used to identify where a PPH occurred after either or both pregnancies.…”
Section: Methodsmentioning
confidence: 99%
“…Canadian and USA studies suggest that such increases are driven by increases in uterine atony, which is purported to be the cause of three‐quarters of postpartum haemorrhages in high resource settings . However, the accuracy of reporting of the cause of PPH has been questioned …”
Section: Introductionmentioning
confidence: 99%